Polymethyl Methacrylate in Patient-Specific Implants: Description of a New Three-Dimension Technique. Issue 2 (March 2019) - Ridwan-Pramana, Angela; Idema, Sander; te Slaa, Sjoerd; Verver, Frank; Wolff, Jan; Forouzanfar, Tymour; Peerdeman, Saskia
Abstract : Abstract: Polymethyl methacrylate (PMMA), an easily moldable and economical synthetic resin, has been used since the 1940s. In addition, PMMA has good mechanical properties and is one of the most biocompatible alloplastic materials currently available. The PMMA can serve as a spacer and as a delivery vehicle for antibiotics. Prior studies have indicated that no significant differences in infection rates exist between autologous and acrylic cranioplasty. Although inexpensive, the free-hand cranioplasty technique often yields unsatisfactory cosmetic results. In the present study, the application of a recently developed, economic modality for the perioperative application, and molding of PMMA to ensure a precise fit in 16 patients using computer-aided design, computer-aided manufacturing, and rapid prototyping was described. The mean defect size was 102.0 ± 26.4 cm 2 . The mean volume of PMMA required to perform the cranioplasty procedure was 51 mL. The cost of PMMA was approximately 6 Euro ([Euro sign]) per mL. The costs of fabricating the implants varied from 119.8 [Euro sign] to 1632.0 [Euro sign] with a mean of 326.4 [Euro sign] ± 371.6. None of the implants required removal during the follow-up period.